Dimensi Kecerdasan dan Dimensi Lingkungan Kerja serta Pengaruhnya terhadap Kinerja Pegawai - Tehubijuluw Zacharias (Syntax Idea)
This study aims to analyze the influence of intelligence dimensions and work environment dimensions on employee performance. This study uses a descriptive-quantitative approach with a causal correlation type. The population used in this study were all employees of the Village Community Empowerment Training Center, Disadvantaged Regions and Ambon Transmigration, totaling 31 people. The sample is determined by full sampling. Data were analyzed using multiple linear regression with the help of SPSS 25.00. The results of the study concluded that (1) emotional intelligence influences employee performance; (2) intellectual intelligence affects employee performance; (3) social intelligence affects employee performance; (4) the physical work environment influences employee performance; (5) non-physical work environment affects employee performance